Determinants of farmer participation in agriculture micro insurance in Zimbabwe. - Chatizah, Loice (Midlands State University, 2020)
The study examined determinants of farmer participation in agriculture micro insurance in Zimbabwe specific reference to peri urban area in Harare. The study was promoted by low uptake of agriculture insurance products being experienced by companies offering agriculture micro insurance. There was need in the market to develop a product that is affordable due to the informalised nature of the Zimbabwean sector. There is need to reach to the poor households and mitigate their level of risks to reduce negative shocks on their assets. The target population were small holder farmers located in the peri urban arrears of Harare and two agriculture micro insurance providers. Sampling techniques used were was stratified random sampling and convenience sampling. The census method of data collection was also included in the research. A mixed research approach was adopted combining both quantitative and qualitative data. An exploratory research design approach was adopted with research data being collected by way of utilizing the questionnaires, interviews and secondary data made available to the researcher by the Zimbabwe farmers Association this data was analysed using Stastical Package of Social Sciences (SPSS). Stepwise regression was then used to establish significant factors that influence the purchasing decisions of small holder farmers. Backward stepwise regression showed that 6 factors out of twelve factors are significant namely, price, trust, wealth and income, government schemes, product design, education and awareness. The other 6 factors were considered insignificant as they had no effect on the dependent variable. The significant factors were fitted in the logistics model regression model to assess the effect of the explanatory variables on farmer participation in agriculture insurance and 86.8% chance was established. The results also show that they was limited knowledge on the insurance products. The study recommended that awareness and education be conducted to the farmers, farmers should be innovative in their farming activities and subsidies/ incentives to be provided by the government so as to increase micro insurance uptake.